Illegal Aliens, Criminals, and Hypersexual Spitfires: Latin@ Youth and Pedagogies of Citizenship in Media Texts. Issue 3 (3rd May 2016) - Bondy, Jennifer M.; Pennington, Lisa K.
ABSTRACT: This article aims to broaden the ways we conceptualize citizenship and implement citizenship education in social studies. To do so, the authors explore media texts as a curricular and pedagogical site for teaching lessons about citizenship. Specifically, the authors investigate how media drafts the boundaries of citizenship for Latin@ youth, and influences how young people come to understand who is and who is not perceived as a citizen entitled to rights and freedoms. Media texts, like formal social studies curricula, are powerful and enduring educators that shape how students know the world and imagine their place in it. Therefore, this article addresses how social studies teachers can integrate media texts into the classroom to explore representations of Latin@s and the impact that media has on our citizenship identities and experiences.